Acquisition of a spatially defined operant with delayed reinforcement. - Critchfield, T S (1993)
Two experiments investigated the role of an immediate, response-produced auditory stimulus during acquisition, via delayed reinforcement, of a response selected to control for possible unprogrammed, operandum-related sources of response feedback. Experimentally naive rats were exposed to a delayed-food reinforcement condition, specifically a tandem fixed-ratio 1 differential-reinforcement-of-other-behavior 30-s schedule. The response was defined as breaking a photocell beam located near the ceiling at the rear of the operant conditioning chamber. In Experiment 1, rates of photobeam breaking by each rat increased from near zero, regardless of the presence or absence of a tone that immediately followed the response initiating the delay interval. Though not essential, the tone facilitated response acquisition and resulted in more efficient response patterns at stability. Experiment 2 demonstrated that photobeam-breaking response rates under the delayed reinforcement contingency exceeded those in a preceding baseline condition in which no food was delivered. In addition, upon introduction of the delayed reinforcement procedure, correspondence between response patterns and the requirements of the reinforcement schedule increased over baseline levels in the absence of a food contingency. Together with a previous report of Lattal and Gleeson (1990), the present results suggest that response acquisition with delayed reinforcement is a robust phenomenon that may not depend on a mechanically defined response or an immediate external stimulus change to mediate the temporal gap between response and reinforcer.